Adaptogens in chemobrain (Part III): antitoxic effects of plant extracts towards cancer chemotherapy-induced toxicity - transcriptome-wide microarray analysis of neuroglia cells - Seo, Ean-Jeong; Klauck, Sabine; Efferth, Thomas; Panossian, Alexander (Phytomedicine, 2019)
Background - Toxicity of chemotherapeutics is a serious problem in cancer therapy. Adaptogens are known to increase adaptability and survival organisms. - Aim - The aim of this study was to assess the effects of selected adaptogenic herbal extracts on FEC (fixed combination of 5-fluorouracil, epirubicin and cyclophosphamide) induced changes in transcriptome-wide microarray profiles of neuroglia cells. Another task of the study was to identify those genes, which are associated with FEC-induced hepato-, cardio- and nephrotoxicity to predict potential effects of andrographolide (AND), Andrographis herb, Eleutherococcus roots genuine extracts (ES), their fixed combination (AE) and the combination of Rhodiola roots, Schisandra berries and Eleutherococcus roots (RSE) on the organismal level. - Methods - Gene expression profiling was performed by transcriptome-wide mRNA microarray in the human T98G neuroglia cells after treatment with adaptogens. Interactive pathways downstream analysis was performed with data sets of significantly up- or down-regulated genes and predicted effects on cellular functions and diseases were identified by Ingenuity IPA database software. - Result - Significant differences of transcriptome-wide microarray profiles were observed after treatment of T98G cells with FEC and after co-incubation with adaptogens. FEC induced deregulation of certain genes with suggested toxicity associated with liver fibroses, necrosis and congenital heart diseases. Co-incubation of AE with FEC prevented FEC-induced deregulation of 66 genes increasing organismal death, 37 genes decreasing cell survival, 37 genes decreasing DNA repair, 37 genes decreasing viral infection and some other functions, indicating on potential beneficial effects of AE. Furthermore, FEC-induced hepato-, nephro- and cardiotoxicity related to deregulation of genes was predictably attenuated by AE. Moreover, co-incubation of AE with FEC caused differential expression of genes, which presumably are beneficial for an organism during chemotherapy. They include predicted activation of DNA repair, activation of movement of antigen presenting cells and inhibition of muscle cells death. The main active constituent of AE is AND. Co-incubation of FEC only with AND results in deregulation of 10 genes causing death of breast cancer cells, decrease of liver toxicity and attenuation of organismal death. Co-incubation of ES extract with FEC showed that ES suppressed FEC-induced deregulation of genes, which inhibit organismal death and fertility. Co-incubation of FEC with RSE indicated potential hepatoprotective effect against FEC-induced apoptosis of liver cells presumably due to suppression of FEC-induced expressions of genes, which increased liver cell apoptosis. Simultaneously, RSE activated expression of genes inhibiting tumor growth. Though, microarray analysis did not provide final proof that the genes induced by the AE, AP and ES are responsible for the physiological effects observed in human patients following their oral administration, it provided insights into putative genes and directions for future research and possible implementation into practice. - Conclusion - Application of cytostatic drugs in combination with adaptogenic plant extracts induced significant changes in transcriptome-wide microarray profiles of neuroglial cells. These changes indicate on potential beneficial effects of adaptogens on FEC induced adverse events in cancer chemotherapy.
Available online 9 November 2018
Gesehen am 24.07.2019